Treatment response, safety, and tolerability of paliperidone extended release treatment in patients recently diagnosed with schizophrenia. (August 2015) - Helldin, Lars; Peuskens, Joseph; Vauth, Roland; Sacchetti, Emilio; bij de Weg, Haye; Herken, Hasan; Lahaye, Marjolein; Schreiner, Andreas
Objective: This study was designed to explore the efficacy and tolerability of oral paliperidone extended release (ER) in a sample of patients who were switched to flexible doses within the crucial first 5 years after receiving a diagnosis of schizophrenia. Methods: Patients were recruited from 23 countries. Adults with nonacute but symptomatic schizophrenia, previously unsuccessfully treated with other oral antipsychotics, were transitioned to paliperidone ER (3–12 mg/day) and prospectively treated for up to 6 months. The primary efficacy outcome for patients switching for the main reason of lack of efficacy with their previous antipsychotic was at least 20% improvement in Positive and Negative Syndrome Scale (PANSS) total scores. For patients switching for other main reasons, such as lack of tolerability, compliance or 'other', the primary outcome was non-inferiority in efficacy compared with the previous oral antipsychotic. Results: For patients switching for the main reason of lack of efficacy, 63.1% achieved an improvement of at least 20% in PANSS total scores from baseline to endpoint. For each reason for switching other than lack of efficacy, efficacy maintenance after switching to paliperidone ER was confirmed. Statistically significant improvement in patient functioning from baseline to endpoint, as assessed by the Personal and Social Performance scale, was observed ( p < 0.0001). Treatment satisfaction with prior antipsychotic treatment at baseline was rated 'good' to 'very good' by 16.8% of patients, and at endpoint by 66.0% of patients treated with paliperidone ER. Paliperidone ER was generally well tolerated, with frequently reported treatment-emergent adverse events being insomnia, anxiety and somnolence. Conclusions: Flexibly dosed paliperidone ER was associated with clinically relevant symptomatic and functional improvement in recently diagnosed patients with non-acute schizophrenia previously unsuccessfully treated with other oral antipsychotics.